Metabolic Profiling of Mice with Deletion of the Orphan G Protein-Coupled Receptor, GPR37L1 - Margaret A. Mouat; Brendan P. Wilkins; Eileen Ding; Hemna Govindaraju; James L. J. Coleman; Robert M. Graham; Nigel Turner; Nicola J. Smith (Cells, 2022)
Understanding the neurogenic causes of obesity may reveal novel drug targets to counter the obesity crisis and associated sequelae. Here, we investigate whether the deletion of GPR37L1, an astrocyte-specific orphan G protein-coupled receptor, affects whole-body energy homeostasis in mice. We subjected male Gpr37l1−/− mice and littermate wildtype (Gpr37l1+/+, C57BL/6J background) controls to either 12 weeks of high-fat diet (HFD) or chow feeding, or to 1 year of chow diet, with body composition quantified by EchoMRI, glucose handling by glucose tolerance test and metabolic rate by indirect calorimetry. Following an HFD, Gpr37l1−/− mice had similar glucose handling, body weight and fat mass compared with wildtype controls. Interestingly, we observed a significantly elevated respiratory exchange ratio in HFD- and chow-fed Gpr37l1−/− mice during daylight hours. After 1 year of chow feeding, we again saw no differences in glucose and insulin tolerance or body weight between genotypes, nor in energy expenditure or respiratory exchange ratio. However, there was significantly lower fat mass accumulation, and higher ambulatory activity in the Gpr37l1−/− mice during night hours. Overall, these results indicate that while GPR37L1 may play a minor role in whole-body metabolism, it is not a viable clinical target for the treatment of obesity.